2004
DOI: 10.1021/la049910a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of the Interplay between Water and Temperature on the Growth of Alkylsiloxane Submonolayers on Silicon

Abstract: We have investigated the influence of the interplay of the temperature and the water concentration in the adsorption solution on the growth of self-assembled monolayers on silicon using octadecyltrichlorosilane as the precursor. Toluene has been used as the solvent. The morphology of the submonolayer films has been investigated by atomic force microscopy (AFM). The surface coverages have been determined both with ellipsometry and through quantitative evaluation of AFM images. The size distribution of species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…[76] Dynamic light scattering studies revealed the formation of aggregates in solution with a hydrodynamic radius of approximately 200 nm for all examined water concentrations and temperatures. However, formation of the aggregates was faster at higher water contents and lower temperatures.…”
Section: Mechanism Of Formationmentioning
confidence: 92%
“…[76] Dynamic light scattering studies revealed the formation of aggregates in solution with a hydrodynamic radius of approximately 200 nm for all examined water concentrations and temperatures. However, formation of the aggregates was faster at higher water contents and lower temperatures.…”
Section: Mechanism Of Formationmentioning
confidence: 92%
“…The exact state of mechanism behind the chemical bonding of OTS on a surface is still debatable. The formation of OTS monolayer on a material surface is highly sensitive to several factors, which include (a) the density of surface hydroxyl groups [32]; (b) reaction temperature [29,33]; (c) reaction environment [34,35]; (d) reaction time [34]; (e) solvent used to deposit OTS [35,36]; (f) water content of the solvent [33]; (g) concentration of OTS [35,37]; (h) solution age [38]; (i) roughness of the underlying substrate [39]; and (j) cleaning procedures after SAM deposition [40].…”
Section: Introductionmentioning
confidence: 99%
“…Glaser et al studied OTS submonolayers and reported that the formation of water aggregates was faster at higher water contents and lower temperatures. A characteristic temperature was found above which the aggregates could no longer be detected and which was higher for higher concentrations [231].…”
Section: Chemistry and Mechanism Of Alkylsilane Sam Formationmentioning
confidence: 96%